Ichthyosis: case report in a Colombian man with genetic alterations in ABCA12 and HRNR genes (2021)
Background: Ichthyosis is a heterogeneous group of diseases caused by genetic disorders related to skin formation. They are characterized by generalized dry skin, scaling, hyperkeratosis and frequently associated with erythroderma. Among its different types, harlequin ichthyosis (HI) stands out due to its severity. HI is caused by mutations in the ABCA12 gene, which encodes essential proteins in epidermal lipid transport, and it helps maintain the homeostasis of the stratum corneum of the epidermis. However, due to the wide spectrum of genetic alterations that can cause ichthyosis, holistic medical care, and genetic studies are required to improve the diagnosis and outcomes of these diseases. Case presentation: Here, we presented the case of a 19 years old male patient who was a premature infant and exhibited clinical features consistent with HI, including bright yellow hyperkeratotic plates with erythematous fissures that covered his entire body like a collodion baby. Currently, he exhibited erythroderma, photosensitivity, ectropion, auricular pavilion alterations, and musculoskeletal disorders, such as equinovarus feet, fingers, hands, and hypoplastic feet with contractures in flexion and marked difficulty in fine motor skills. In addition, he presented dyschromatopsia, Achilles reflex hyporeflexia, slight speech, dental alteration and deficient cognitive performance. After the genetic sequencing, variants were found in ABCA12 and HRNR which are related to several skin diseases, including ichthyosis. Conclusions: Although in clinical practice, ichthyosis is a common entity, a severe type of ichthyosis is presented, highlighting the importance of appropriate genetic diagnosis, given the broad spectrum of genetic alterations with similar phenotypic and clinical characteristics. These pathologies must be known to guarantee initial support measures to prevent complications and offer multidisciplinary management to those patients. Keywords: Harlequin ichthyosis, Congenital ichthyosis, Ichthyosis, Skin disease, Case report